Evaluation of the association between drug use and sleep quality in shift workers vs daytime workers - Rosado, Magda; Carvalho, Lucinda; Coelho, André (Seven Editora, 2023)
Sleep is a physiological process and a fundamental biological function for human survival1. Disturbances in its quality can trigger significant changes in the quality of life of the individual2 . The quality of sleep can be influenced by several factors, such as: previous medical conditions, the consumption of medications and/or stimulant substances, working hours, among others3. The use of medication to alleviate sleep disorders caused by working hours is common; however, if abused and unsupervised, it can trigger new pathological conditions4. On the other hand, when prescribing medications for several pathologies, it is common to neglect their adverse effects on sleep4. DOI: https://doi.org/10.56238/thebestiimulti2022-002